1995
DOI: 10.1113/jphysiol.1995.sp021092
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and release of an acetylcholine‐like compound by human myoblasts and myotubes.

Abstract: 1. Exogenously applied acetylcholine (ACh) is a modulator of human myoblast fusion. Using a chemiluminescent method, we examined whether an endogenous ACh‐like compound (ACh‐lc) was present in, and released by, pure human myogenic cells. 2. Single, freshly isolated satellite cells and proliferating myoblasts contained 15 and 0.5 fmol ACh‐lc, respectively. Cultured myotubes contained ACh‐lc as well. Also, ACh‐like immunoreactivity was detected in all myogenic cells. 3. Part of the ACh‐lc was synthesized by chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 47 publications
4
31
0
Order By: Relevance
“…However, an up-regulation of T-channel expression immediately after fusion cannot be excluded. Another explanation for the low percentage of fusion-competent myoblasts with high [Ca 2ϩ ] i is that myoblasts normally stimulate one another by autocrine mechanisms (31) and that this is less likely to occur in low density cultures. Finally, as we shall discuss below, it is also possible that the [Ca 2ϩ ] i oscillates in fusioncompetent myoblasts so that, at a given time, only a fraction of the cells can be detected with a high [Ca 2ϩ ] i .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an up-regulation of T-channel expression immediately after fusion cannot be excluded. Another explanation for the low percentage of fusion-competent myoblasts with high [Ca 2ϩ ] i is that myoblasts normally stimulate one another by autocrine mechanisms (31) and that this is less likely to occur in low density cultures. Finally, as we shall discuss below, it is also possible that the [Ca 2ϩ ] i oscillates in fusioncompetent myoblasts so that, at a given time, only a fraction of the cells can be detected with a high [Ca 2ϩ ] i .…”
Section: Discussionmentioning
confidence: 99%
“…A Ca 2ϩ -ATPase muscle-specific isoform is expressed at myotube formation in mouse C2 myoblasts (32). Another possible way of reducing Ca 2ϩ entry would be the activation of Ca Interestingly, an effect of the window T-current could be mediated by an acetylcholine-like compound that human myoblasts synthesize and release in a Ca 2ϩ dependent way (31). As acetylcholine has been shown to accelerate fusion (16), Ca 2ϩ entering through the window of the ␣1H T-channel of fusioncompetent myoblasts could trigger release of this compound and thereby favor differentiation of neighboring cells, or contribute to further increase [Ca 2ϩ ] i through muscle nicotinic acetylcholine receptors, which are permeable to Ca 2ϩ (33).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that acetylcholine could be synthesised in myoepithelial cells. This is not entirely surprising because ChAT has been found in nonneuronal human tissues, namely ejaculated spermatozoa (Ibanez et al 1991), myoblasts and myotubes (Hamann et al 1995) and the chorion (Oda et al 1996). Myoepithelial cells subserve the rapid excretion of sweat on stimulation and\or ' provide mechanical support for the secretory coil wall against the increase in luminal hydrostatic pressure ' (Sato et al 1989), and the ChAT activity therein could contribute to regulation of contractile activity.…”
Section: mentioning
confidence: 99%
“…Later, Hamann et al (76) found that proliferating myoblasts contained a small amount of ACh-like compound and that this compound was synthesized by BrACh-sensitive ChAT in all myogenic cells. The ACh-like compound was spontaneously released from both myoblasts and myotubes in a partially Ca 2+ -dependent manner.…”
Section: -8-4 Skeletal Musclementioning
confidence: 99%